Examining The Integration Of Religious Moderation Values Within The Indonesian School Curriculum In Kota Kinabalu, Malaysia: A Cross-Border Educational Perspective - Hudin, Miftah; Rifa'i, Muhadditsir; Munjiat, Siti Maryam; Prasetiyo, Nova Tri (Institut Agama Islam An-Nawawi Purworejo, 2024)
Sekolah Indonesia Kota Kinabalu (SIKK) in Malaysia is an educational institution where the majority of students are children of migrant workers who work in local factories. With diverse ethnic, racial, religious and cultural backgrounds, the values of religious moderation are very suitable to guide students and the school community to have mutual respect and uphold tolerance. This study aims to determine the implementation of religious moderation values in the SIKK curriculum in Malaysia. The method used is descriptive qualitative with observation, interview, and documentation techniques. The results showed that the SIKK curriculum has integrated the values of religious moderation, which are applied in learning, extracurricular activities, and daily habits. Some activities that support the application of these values include IMTAQ activities, 5S culture, SIKK berta'lim program, and Wednesday Culture. This research is limited to various school levels, ranging from early childhood education to senior high school. For more in-depth results, future research is recommended to focus on one level of education. The integration of religious moderation values in the SIKK curriculum is important to support the goals of Islamic Education in forming a tolerant and multicultural-minded generation, as well as supporting social harmony across cultures and religions.